2017
DOI: 10.1016/j.it.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Next-Generation Dendritic Cell Vaccines into the Current Cancer Immunotherapy Landscape

Abstract: Cancer immunotherapy is experiencing a renaissance spearheaded by immune checkpoint inhibitors (ICIs). This has spurred interest in 'upgrading' existing immunotherapies that previously experienced only sporadic success, such as dendritic cells (DCs) vaccines. In this review, we discuss the major molecular, immunological, and clinical determinants of existing first- and second-generation DC vaccines. We also outline the future trends for next-generation DC vaccines and describe their major hallmarks and prerequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
277
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(280 citation statements)
references
References 97 publications
(160 reference statements)
0
277
0
3
Order By: Relevance
“…From a small amount of peripheral blood, one can usually obtain sufficient numbers (approximately 1 × 10 5 to 1 × 10 7 cells/kg body weight) of activated antigen-presenting B cells [35, 51], whereas the generation of DCs typically requires a leukapheresis [52-55]. It has been shown that this is even feasible in cancer patients [35, 51].…”
Section: B Cells For Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…From a small amount of peripheral blood, one can usually obtain sufficient numbers (approximately 1 × 10 5 to 1 × 10 7 cells/kg body weight) of activated antigen-presenting B cells [35, 51], whereas the generation of DCs typically requires a leukapheresis [52-55]. It has been shown that this is even feasible in cancer patients [35, 51].…”
Section: B Cells For Immunotherapymentioning
confidence: 99%
“…However, the current excitement about the success of immune checkpoint blockade in the treatment of a broad range of malignancies has sparked a renaissance of cancer vaccines [52]. Currently, several clinical trials are investigating the combination of DC vaccines with checkpoint inhibitors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Cancer vaccines are aimed at inducing durable anti‐tumor immunity for systemic protection against tumor recurrence or metastasis . Various anti‐glioma vaccines have been developed; one strategy involves the administration of dendritic cell (DC)‐based vaccines, in particular, autologous DCs containing glioma‐associated peptides or whole tumor lysate.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and ability to induce antitumor responses have clearly been established for DC vaccination and patients with long‐term benefit have been reported . Still, DC vaccines have not yet fulfilled their promise and still face several challenges as only a small number of injected DCs migrate to draining lymph nodes and their optimal activation is critical . Recent evidence from DC‐based vaccinations against melanoma suggests that efficacy depends on several factors such as the mode of antigen loading, the maturation‐state of the DCs, the site of injection and the vaccination schedule .…”
Section: Introductionmentioning
confidence: 99%